Fe-Vacancy-Ordered Fe4Se5: The Insulating Parent Phase of FeSe Superconductor - Yeh, Keng-Yu; Chen, Yan-Ruei; Lo, Tung-Sheng; Wu, Phillip M.; Wang, Ming-Jye; Chang-Liao, Kuei-Shu; Wu, Maw-Kuen (Frontiers in Physics, 2020)
We have carried out a detailed study to investigate the existence of an insulating parent phase for FeSe superconductor. The insulating Fe4Se5 with √5 × √5 Fe-vacancy order shows a 3D-Mott variable range hopping behavior with a Verwey-like electronic correlation at around 45 K. The application of the RTA process at 450 °C results in the destruction of Fe-vacancy order and induces more electron carriers by increasing the Fe3+ valence state. Superconductivity emerges with Tc ~ 8K without changing the chemical stoichiometry of the sample after the RTA process by resulting in the addition of extra carriers in favor of superconductivity.